Gradient hydrophilic and hydrophobic carbon paper and preparation method thereof
By constructing gradient hydrophilicity in the thickness direction of carbon paper, and using the attractive effect of hydrophilic pores on liquid water to achieve directional movement, the problem of insufficient drainage capacity of existing carbon paper is solved, and the drainage and gas transmission performance of fuel cells is significantly improved .
Patent Information
- Application Number
- CN202411565947.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The drainage capacity of existing carbon paper is insufficient, resulting in the accumulation of liquid water at high current density, blocking pores, affecting gas diffusion, and limiting the improvement of fuel cell performance.
By constructing gradient hydrophilicity in the thickness direction of carbon paper, the directional movement is achieved by using the attraction effect of hydrophilic pores on liquid water, thereby improving the drainage capacity of carbon paper. The specific method includes immersing the pretreated carbon paper in a nano-silica dispersion for hydrophilic treatment, and then spraying a hydrophobic modified silane dispersion on one side surface, and performing heat treatment to form a gradient hydrophobicity.
It significantly improves the drainage capacity of carbon paper, reduces the saturation of liquid water, ensures smooth gas transmission, improves the output performance of fuel cells, and avoids the defect of sacrificing the effective area of carbon paper.
Smart Images

Figure CN119434018A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a gradient hydrophilic-hydrophobic carbon paper and a preparation method thereof. Background Art
[0002] A fuel cell is a device that converts chemical energy stored in oxidants and reductants into electrical energy through electrochemical reactions. Fuel cells are mainly composed of bipolar plates and membrane electrode assemblies, among which the gas diffusion layer is one of the key components of the membrane electrode assembly. It not only supports the catalyst layer, conducts electricity and heat, but also has the important function of providing gas transmission channels and drainage channels for the electrode reactions of the catalyst layer. With the increasing requirements for the energy density of fuel cells, high current density has become a trend in the development of fuel cells. However, high current density will lead to the generation of a large amount of liquid water. In order to maintain the reaction of the catalyst layer, the water generated by the reaction needs to be discharged from the gas diffusion layer in time to prevent flooding.
[0003] Carbon paper is the most commonly used gas diffusion layer material. It is a porous material composed of carbon fibers. The stacked carbon fibers can provide a certain mechanical strength and play a role in supporting the membrane electrode. At the same time, the carbon fibers also have good electrical and thermal conductivity. More importantly, a large number of micropores are formed between the stacked carbon fibers, providing sufficient channels for gas transmission and drainage. However, existing studies have shown that the insufficient drainage capacity of carbon paper is one of the main factors limiting the performance of fuel cells at high current density. At high current density, liquid water easily accumulates in carbon paper, blocks pores, and affects gas diffusion. Therefore, improving the drainage capacity of carbon paper is crucial to improving the performance of fuel cells. The hydrophilicity and hydrophobicity of carbon paper have an important influence on its drainage capacity. Under the action of surface energy, hydrophobic carbon paper can promote the discharge of liquid water from micropores, while hydrophilic carbon paper attracts liquid water into micropores. By regulating the hydrophilicity and hydrophobicity of carbon paper, the drainage capacity of carbon paper can be significantly enhanced, the drainage efficiency can be improved, thereby ensuring the smooth transmission of reaction gases and ultimately improving the output performance of fuel cells.
[0004] The carbon paper used in fuel cells reported in existing literature is mainly carbon paper with uniform hydrophobicity, but in this type of carbon paper, the movement of liquid water is non-directional, which will cause more pores to be occupied by water in the process of water being discharged from the catalyst layer to the flow channel, and ultimately hinder the transmission of gas. Compared with carbon paper with uniform hydrophobicity, carbon paper with gradient hydrophilicity has more advantages in drainage and gas transmission. Carbon paper with gradient hydrophilicity can use the attraction of hydrophilic pores to liquid water to achieve directional movement of liquid water, thereby greatly improving the drainage capacity of carbon paper, reducing liquid water saturation, and ensuring smooth gas transmission. At present, some literature has reported a method for constructing gradient hydrophilicity in the plane direction of carbon paper, such as patent CN110890555A, etc., by setting a hydrophilic area in a part of the carbon paper plane to promote liquid water movement, thereby reducing the aggregation of liquid water in other areas, but this method needs to sacrifice a part of the effective area of the carbon paper as a hydrophilic area, which is not conducive to the improvement of the overall performance of the battery.
[0005] Patent CN202310287947.4 discloses a method for preparing hydrophilic-hydrophobic carbon paper for fuel cells, which comprises uniformly coating one side of the pretreated carbon paper with polymer latex 1; drying, washing with dilute hydrochloric acid or dilute sulfuric acid for 2 hours, or strengthening by bubbling washing to form a surface modification layer; uniformly coating polymer latex 2 again; placing the carbon paper with a double-layer film with the film facing upward in an electrolytic cell for pulsed electrolysis; the resulting carbon is highly flexible, not easy to lose carbon powder, has excellent electrical conductivity, and has excellent drainage performance. However, the hydrophobic layer of this technology is essentially an additional microporous layer coated on the surface of the carbon paper substrate, and the carbon paper substrate is made hydrophilic by electrolysis. It can only construct a carbon paper substrate with uniform hydrophilicity, and the drainage performance of the carbon paper substrate needs to be further improved. Summary of the invention
[0006] The purpose of the present invention is to provide a gradient hydrophilic and hydrophobic carbon paper and a preparation method thereof in order to overcome the defects of the above-mentioned prior art, thereby constructing a gradient hydrophilicity in the thickness direction of the carbon paper, thereby directionally guiding the liquid water in the carbon paper to move from the catalytic layer side to the flow channel side, and further helping to comprehensively improve the drainage capacity of the carbon paper while avoiding sacrificing the effective area of the carbon paper.
[0007] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing gradient hydrophilic and hydrophobic carbon paper, comprising the following steps:
[0008] (1) immersing the pretreated carbon paper in a nano-silicon dioxide dispersion, taking it out, drying it, and performing a heat treatment to obtain a hydrophilic carbon paper;
[0009] (2) Spraying a hydrophobically modified silane dispersion on one surface of the hydrophilic treated carbon paper, drying it, and then performing a heat treatment to obtain a carbon paper having a gradient hydrophilicity and hydrophobicity in the thickness direction.
[0010] Furthermore, the pretreatment method of the carbon paper in step (1) is: cleaning the carbon paper, removing dust on the surface and then drying the carbon paper to obtain pretreated carbon paper.
[0011] Furthermore, the nano-silicon dioxide dispersion in step (1) is prepared by the following method: dispersing nano-silicon dioxide in a dispersant to obtain a nano-silicon dioxide dispersion with a mass concentration of 0.1 wt% to 10 wt%.
[0012] Furthermore, the particle size of the nano-silicon dioxide is 20nm to 200nm, and the dispersant is one or more of ethanol, isopropanol or deionized water.
[0013] Furthermore, the heat treatment temperature in step (1) is 100° C. to 200° C.; the heat treatment time is 30 min to 120 min; after the treatment, the hydrophilic nano-silica is combined with the carbon fiber surface of the carbon paper to achieve hydrophilic modification of the carbon paper.
[0014] Furthermore, the hydrophobically modified silane dispersion in step (2) is prepared by the following method: dispersing silane in a dispersant to prepare a hydrophobically modified silane dispersion with a volume concentration of 0.01% to 1%.
[0015] Furthermore, the silane includes one or more of perfluorodecyltriethoxysilane, perfluorooctyltriethoxysilane, perfluorooctyltrichlorosilane, and hexadecyltrimethoxysilane, and the dispersant is one or more of ethanol and isopropanol.
[0016] Furthermore, the amount of the silane dispersion sprayed in step (2) is 0.1 ml / cm 2 ~100ml / cm 2 According to the different spraying amounts, carbon paper with different hydrophilic and hydrophobic gradients in the thickness direction was obtained.
[0017] Furthermore, in step (2), the heat treatment temperature is 80°C to 150°C; the heat treatment time is 30min to 120min; after treatment, the hydrophobically modified silane reacts with the nano-silica on the surface of the carbon fiber on one side of the carbon paper to achieve hydrophobic modification of one side of the carbon paper, thereby obtaining carbon paper with gradient hydrophilicity and hydrophobicity in the thickness direction.
[0018] The invention also provides a gradient hydrophilic-hydrophobic carbon paper prepared by the method.
[0019] The gradient hydrophilic-hydrophobic carbon paper and its preparation method provided by the present invention at least include the following advantages compared with the prior art:
[0020] Beneficial effects:
[0021] 1) The present invention uses hydrophilic nano-silica and hydrophobic silane to modify carbon paper, so as to prepare carbon paper with gradient hydrophilicity and hydrophobicity in the thickness direction. The hydrophilicity changes gradually in the thickness direction, which can effectively improve the drainage capacity of the carbon paper, thereby enhancing the gas transmission capacity and improving the mass transfer performance of the carbon paper.
[0022] 2) The present invention adopts a method of first subjecting the carbon paper to overall hydrophilic treatment and then spraying a hydrophobic modifier on one side to form a gradient hydrophilicity in the thickness direction. The hydrophilicity gradient can be effectively regulated by simply adjusting the amount of the hydrophobic modifier sprayed on one side, and carbon paper with different hydrophilicity gradients in the thickness direction can be quickly prepared.
[0023] 3) The present invention realizes the hydrophilic and hydrophobic modification of carbon paper by combining hydrophilic nano-silica on the surface of carbon fiber and then grafting hydrophobic silane onto the surface of nano-silica. This method avoids the influence of high-temperature heat treatment or other chemical treatment on the performance of carbon materials, and at the same time, the stability of the hydrophobic performance of the material can be effectively improved by chemically grafting the hydrophobic agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The SEM images of the carbon fibers inside the untreated carbon paper and the carbon fibers inside the carbon paper after hydrophilic and hydrophobic modification;
[0025] Figure 2 The contact angle pictures of the untreated carbon paper and the contact angle pictures of the hydrophilic side and the hydrophobic side of the carbon paper after the hydrophilic-hydrophobic modification treatment in Example 1;
[0026] Figure 3 The contact angle images of the hydrophilic side and the hydrophobic side of the carbon paper after the hydrophilic-hydrophobic modification treatment in Example 2;
[0027] Figure 4 The contact angle images of the hydrophilic side and the hydrophobic side of the carbon paper after the hydrophilic-hydrophobic modification treatment in Example 3;
[0028] Figure 5 The contact angle images of the hydrophilic side and the hydrophobic side of the carbon paper after the hydrophilic-hydrophobic modification treatment in Example 4;
[0029] Figure 6 The performance polarization curves of the carbon paper after hydrophilic-hydrophobic modification in Example 1 and the conventional uniformly hydrophobic carbon paper in a hydrogen-air fuel cell are shown. DETAILED DESCRIPTION
[0030] The present invention provides a gradient hydrophilic-hydrophobic carbon paper and a preparation method thereof. The hydrophilic-hydrophobic gradient is shown in the thickness direction of the carbon paper to improve the drainage capacity of the carbon paper. In addition, by regulating the preparation process, the hydrophilic-hydrophobic gradient can also be effectively regulated to prepare carbon paper with different hydrophilic-hydrophobic gradients in the thickness direction according to the needs of different usage scenarios. The specific method includes the following steps:
[0031] (1) Soak the carbon paper in acetone or ethanol for 5-15 minutes, then clean it with deionized water to remove dust on the surface and dry it to obtain pretreated carbon paper;
[0032] (2) The pretreated carbon paper is immersed in a nano-silicon dioxide dispersion having a mass concentration of 0.1wt% to 10wt%, the number of immersions being 1 to 3 times, the immersion time being 0.5 to 5 minutes, the carbon paper is taken out, dried at room temperature or vacuum dried, and then heat-treated at 100°C to 200°C for 30 minutes to 120 minutes to obtain hydrophilic carbon paper, and the bonding force between the nano-silicon dioxide and the carbon fiber is increased by heat treatment; the nano-silicon dioxide dispersion can be prepared by a sol-gel method, or by ultrasonically dispersing nano-silicon dioxide powder in a dispersant composed of one or more of ethanol, isopropanol or deionized water.
[0033] (3) Spraying a hydrophobically modified silane dispersion with a volume concentration of 0.01% to 1% on the surface of one side of the hydrophilic treated carbon paper, drying, and heat treating at 80°C to 150°C for 30min to 120min to obtain a carbon paper with gradient hydrophilicity and hydrophobicity in the thickness direction. The heat treatment promotes the chemical reaction between silane and nano-silica so that it is grafted onto the surface of nano-silica. The silane used in the hydrophobically modified silane dispersion includes one or more long-chain silanes with hydrophobic modification such as perfluorodecyltriethoxysilane, perfluorooctyltriethoxysilane, perfluorooctyltrichlorosilane, and hexadecyltrimethoxysilane. The dispersant used is one or more of ethanol and isopropanol. The spraying method includes manual spraying, ultrasonic spraying, electrostatic spraying, etc. The amount of the sprayed silane dispersion is 0.1ml / cm 2 ~100ml / cm 2 .
[0034] The raw materials used in the present invention are all commercially available raw materials in the art, and the equipment or devices used are all conventional equipment or devices.
[0035] Example 1
[0036] Take 5×5cm 2Carbon paper with a thickness of 0.18 mm was soaked in acetone for 10 min and then cleaned with deionized water. It was placed in a vacuum drying oven and vacuum dried for 30 min to obtain pretreated carbon paper.
[0037] Take a 200 ml reactor, add 50 ml of anhydrous ethanol, then add 4 g of nano-silicon dioxide powder with a particle size of 50 nm, and use an ultrasonic cell disruptor to perform ultrasonic dispersion for 30 minutes to obtain a nano-silicon dioxide dispersion. After the pretreated carbon paper is immersed in the nano-silicon dioxide dispersion for 1 minute, the carbon paper is taken out and placed in a vacuum drying oven for vacuum drying for 30 minutes.
[0038] Take a 50ml reactor, add 20ml of anhydrous ethanol, then add 0.05ml of perfluorooctyltrichlorosilane, use an ultrasonic cleaner to perform ultrasonic dispersion for 30min to obtain a silane dispersion. After spraying 20ml of the silane dispersion on one side of the hydrophilic carbon paper by ultrasonic spraying, place the carbon paper in a vacuum drying oven for vacuum drying for 30min, and then place the carbon paper in an oven for heat treatment at 80℃ for 1h to obtain a carbon paper with gradient hydrophilicity in the thickness direction.
[0039] The microstructure of the prepared carbon paper was observed by scanning electron microscopy (SEM). Figure 1 . In contrast, Figure 1 The SEM images of the untreated carbon paper are also given. Figure 1 It can be seen that after the treatment of carbon paper, nano-silica entered the gaps of carbon fibers and adhered to the carbon fibers.
[0040] The contact angle of the prepared carbon paper was tested using a contact angle meter. The results are shown in Figure 3 For comparison, the contact angle picture of the untreated carbon paper is also given. The contact angle of the hydrophilic side of the treated carbon paper is about 66°, and the contact angle of the hydrophobic side is about 145°, while the contact angle of the untreated carbon paper with water is about 118°.
[0041] Example 2
[0042] Take 5×5cm 2 Carbon paper with a thickness of 0.18 mm was soaked in acetone for 10 min and then cleaned with deionized water. It was placed in a vacuum drying oven and vacuum dried for 30 min to obtain pretreated carbon paper.
[0043] Take a 200ml reactor, add 50ml of anhydrous ethanol, then add 2g of nano-silicon dioxide powder with a particle size of 20nm, and use an ultrasonic cell disruptor for ultrasonic dispersion for 30min to obtain a nano-silicon dioxide dispersion. After the pretreated carbon paper is immersed in the nano-silicon dioxide dispersion for 1min, the carbon paper is taken out and placed in a vacuum drying oven for vacuum drying for 30min, the immersion and drying are repeated twice, and then the carbon paper is placed in an oven and heat treated at 120℃ for 1h to obtain hydrophilic carbon paper. Take a 50ml reactor, add 20ml of anhydrous ethanol, then add 0.05ml of perfluorooctyltrichlorosilane, and use an ultrasonic cleaner for ultrasonic dispersion for 30min to obtain a silane dispersion. After spraying 10ml of silane dispersion on one side of the hydrophilic carbon paper by ultrasonic spraying, the carbon paper is placed in a vacuum drying oven for vacuum drying for 30min, and then the carbon paper is placed in an oven and heat treated at 80℃ for 1h to obtain a carbon paper with gradient hydrophilicity in the thickness direction.
[0044] The contact angle of the prepared carbon paper was tested using a contact angle meter. The results are shown in Figure 3 The contact angle of the hydrophilic side of the treated carbon paper is about 36°, and the contact angle of the hydrophobic side is about 130°.
[0045] Example 3
[0046] Take 5×5cm 2 A 0.18mm thick carbon paper is soaked in acetone for 10 minutes and then cleaned with deionized water. It is placed in a vacuum drying oven and vacuum dried for 30 minutes to obtain the pretreated carbon paper. A 200ml reactor is taken and 50ml of 2.5wt% nano-silicon dioxide ethanol dispersion is prepared by sol-gel method. The particle size of the nano-silicon dioxide is between 20-100nm. After the pretreated carbon paper is immersed in the nano-silicon dioxide dispersion for 1 minute, the carbon paper is taken out and placed in a vacuum drying oven for vacuum drying for 30 minutes. The immersion and drying are repeated 3 times, and then the carbon paper is placed in an oven and heat treated at 120°C for 1 hour to obtain hydrophilic carbon paper. A 50ml reactor is taken, 20ml of anhydrous ethanol is added, and then 0.1ml of perfluorodecyltriethoxysilane is added. Ultrasonic dispersion is performed using an ultrasonic cleaner for 30 minutes to obtain a silane dispersion. After spraying 10 ml of silane dispersion on one side of the hydrophilic carbon paper by ultrasonic spraying, the carbon paper was placed in a vacuum drying oven for vacuum drying for 30 minutes, and then placed in an oven for heat treatment at 80°C for 1 hour to obtain carbon paper with gradient hydrophilicity and hydrophobicity in the thickness direction.
[0047] The contact angle of the prepared carbon paper was tested using a contact angle meter. The results are shown in Figure 4 The contact angle of the hydrophilic side of the treated carbon paper is about 48°, and the contact angle of the hydrophobic side is about 133°.
[0048] Example 4
[0049] Take 5×5cm 2 Carbon paper with a thickness of 0.18 mm is soaked in acetone for 10 minutes, then cleaned with deionized water, and placed in a vacuum drying oven for vacuum drying for 30 minutes to obtain pretreated carbon paper. Take a 200 ml reactor, add 50 ml of anhydrous ethanol, and then add 2 g of nano-silicon dioxide powder with a particle size of 20 nm, and use an ultrasonic cell disruptor for ultrasonic dispersion for 30 minutes to obtain a nano-silicon dioxide dispersion. After the pretreated carbon paper is immersed in the nano-silicon dioxide dispersion for 1 minute, the carbon paper is taken out and placed in a vacuum drying oven for vacuum drying for 30 minutes, and the immersion and drying are repeated twice, and then the carbon paper is placed in an oven and heat treated at 120 ° C for 1 hour to obtain hydrophilic carbon paper. Take a 50 ml reactor, add 20 ml of anhydrous ethanol, and then add 0.15 ml of perfluorooctyltrichlorosilane, and use an ultrasonic cleaner for ultrasonic dispersion for 30 minutes to obtain a silane dispersion. After spraying 10 ml of silane dispersion on one side of the hydrophilic carbon paper by ultrasonic spraying, the carbon paper was placed in a vacuum drying oven for vacuum drying for 30 minutes, and then placed in an oven for heat treatment at 80°C for 1 hour to obtain carbon paper with gradient hydrophilicity and hydrophobicity in the thickness direction.
[0050] The contact angle of the prepared carbon paper was tested using a contact angle meter. The results are shown in Figure 5 The contact angle of the hydrophilic side of the treated carbon paper is about 81°, and the contact angle of the hydrophobic side is about 145°.
[0051] The carbon paper with gradient hydrophilicity and hydrophobicity prepared in Example 1 was used in a hydrogen-air fuel cell for testing. The hydrogen-air fuel cell used was a conventional hydrogen-air fuel cell in the art. The battery included a proton exchange membrane, a positive and negative catalyst layer, a positive and negative hydrophobic microporous layer, a positive and negative carbon paper (the carbon paper prepared in Example 1 was used, and a conventional uniform hydrophobic carbon paper was used as a comparative example), and a battery bipolar plate with a serpentine flow channel. The catalyst layer used a conventional platinum catalyst, and the platinum loading of the positive catalyst layer was 0.1 mg / cm 2 The platinum loading of the cathode catalyst layer is 0.4 mg / cm 2 The effective reaction area of the battery is 16 cm 2 The anode humidity was controlled at 60%, the cathode humidity was controlled at 20%, the anode stoichiometric ratio was controlled at 1.5, the cathode stoichiometric ratio was controlled at 1.8, the anode back pressure was controlled at 170KPa, the cathode back pressure was controlled at 150KPa, and the battery temperature was controlled at 80°C. The battery performance test results are shown in Figure 6As shown in the figure, under high current density conditions, the mass transfer loss of the battery using the gradient hydrophilic and hydrophobic carbon paper is smaller and the battery output voltage is higher. This is because the gradient hydrophilic and hydrophobic carbon paper has a stronger drainage capacity and is less likely to be flooded. Its performance is better than that of the conventional uniform hydrophobic carbon paper of the same specifications.
[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the invention patent should be included in the protection scope of the invention patent.
Claims
1. A method for preparing gradient hydrophilic-hydrophobic carbon paper, characterized in that: The following steps are involved: (1) immersing the pretreated carbon paper in a nano-silicon dioxide dispersion, taking it out, drying it, and performing a heat treatment to obtain a hydrophilic carbon paper; (2) Spraying a hydrophobically modified silane dispersion on one surface of the hydrophilic treated carbon paper, drying it, and then performing a heat treatment to obtain a carbon paper having a gradient hydrophilicity and hydrophobicity in the thickness direction.
2. The method for preparing a gradient hydrophilic-hydrophobic carbon paper according to claim 1, characterized in that: The carbon paper pretreatment method in step (1) is as follows: the carbon paper is cleaned, dust on the surface is removed, and then the carbon paper is dried to obtain the pretreated carbon paper.
3. The method for preparing a gradient hydrophilic-hydrophobic carbon paper according to claim 1, characterized in that: The nano-silicon dioxide dispersion in step (1) is prepared by the following method: dispersing nano-silicon dioxide in a dispersant to obtain a nano-silicon dioxide dispersion with a mass concentration of 0.1wt% to 10wt%.
4. The method for preparing a gradient hydrophilic-hydrophobic carbon paper according to claim 3, characterized in that: The particle size of the nano silicon dioxide is 20nm-200nm, and the dispersant is one or more of ethanol, isopropanol or deionized water.
5. The method for preparing a gradient hydrophilic-hydrophobic carbon paper according to claim 1, characterized in that: The heat treatment temperature in step (1) is 100° C. to 200° C.; the heat treatment time is 30 min to 120 min; after the treatment, the hydrophilic nano-silica is combined with the carbon fiber surface of the carbon paper to achieve hydrophilic modification of the carbon paper.
6. The method for preparing a gradient hydrophilic-hydrophobic carbon paper according to claim 1, characterized in that: The hydrophobically modified silane dispersion in step (2) is prepared by the following method: dispersing silane in a dispersant to prepare a hydrophobically modified silane dispersion with a volume concentration of 0.01% to 1%.
7. The method for preparing a gradient hydrophilic-hydrophobic carbon paper according to claim 6, characterized in that: The silane includes one or more of perfluorodecyltriethoxysilane, perfluorooctyltriethoxysilane, perfluorooctyltrichlorosilane, and hexadecyltrimethoxysilane, and the dispersant is one or more of ethanol and isopropanol.
8. The method for preparing a gradient hydrophilic-hydrophobic carbon paper according to claim 1, characterized in that The amount of silane dispersion sprayed in step (2) is 0.1 ml / cm 2 ~100ml / cm 2 According to the different spraying amounts, carbon paper with different hydrophilic and hydrophobic gradients in the thickness direction was obtained.
9. The method for preparing a gradient hydrophilic-hydrophobic carbon paper according to claim 1, characterized in that: In step (2), the heat treatment temperature is 80° C. to 150° C.; the heat treatment time is 30 min to 120 min. After the treatment, the hydrophobically modified silane reacts with the nano-silicon dioxide on the surface of the carbon fiber on one side of the carbon paper to achieve hydrophobic modification on one side of the carbon paper, thereby obtaining carbon paper with gradient hydrophilicity and hydrophobicity in the thickness direction.
10. A gradient hydrophilic-hydrophobic carbon paper prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of diffusion layer with gradient hydrophilicity or hydrophobicity
CN110890555A
A method for preparing hydrophilic-hydrophobic carbon paper for fuel cells
CN116377759B
Hydrophobic paper and preparation method thereof
CN105463926A
Hydrophilic treatment method of carbon paper for fuel cell and application thereof
CN111244476A
Preparation method of easy-to-coat fluorocarbon nano hydrophobic coating and product of easy-to-coat fluorocarbon nano hydrophobic coating
CN112662309A
Cited By
Long-acting hydrophilic modification method for porous foamy copper and application of long-acting hydrophilic modification method in evaporation heat exchanger
CN121402303A